Program Online Scholarship Competition Sebagai Wujud Partisipasi Penciptaan Generasi Emas Indonesia 2045 - Indrati, Imam; Islam, Muhammad; Paramita, Adianti (Universitas Pendidikan Ganesha, 2020)
This study aims to evaluate the OSC Program in terms of the mechanism of obtaining scholarships through the online scholarship competition program, and the obstacles faced when screening scholarship candidates. Field observations and interviews are used to collect data, and PESTEL and SWOT techniques are collaborated to identify the strengths, weaknesses, opportunities, and threats. The results show that this program has legitimacy and is officially supported by the Ministry of Research, Technology and Higher Education. Futhermore, OSC has a very clear, segmented and national target market. For private universities and sponsorships that are incorporated can raise the brand image of PTS and scholarship fund companies.